PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE TGT (TEAMS GAMES TOURNAMENT) DISERTAI KARTU DOMINO MODIFIKASI TERHADAP HASIL BELAJAR SISWA KELAS X SMA N 1 KIBANG PADA MATERI RUANG LINGKUP BIOLOGI - Ahmad Dwiki Prasetyo; Handoko Santoso; Agil Lepiyanto (Prodi Pendidikan Biologi FKIP Universitas Muhammadiyah Metro, 2021)
The combination of learning models and media aims to make learning goals easily achieved by students. The TGT (Teams Games Tournament) model can involve students actively in learning, students are required to work in groups, create an atmosphere of learning into a game and there is competition which will be given an award or reward. Modified dominoes can make it easier for students to understand the concepts of the material being studied, as well as an attractive display of modification dominoes can make students not get bored in the learning process. The aims of this study was to determine the effect of the TGT (Teams Games Tournament) cooperative learning model accompanied by modified domino cards on learning outcomes in the biology scope material of Grade X of SMA 1 Kibang.This type of research is a quasi experiment with Posttest only Control Group Design. The place of research is SMA 1 Kibang. The population in this study were all students of class X with a total of 85 students consisting of 3 classes. The sample used in this study was two classes namely X MIPA 1 and X MIPA 2. X MIPA 1 became a control class consisting of 29 students, while class X MIPA 2 became an experimental class consisting of 28 students. This research was conducted on July 19 - August 7, 2019. The prerequisite test in this study used the normality and homogeneity test. Hypothesis testing using t test. Based on the results of hypothesis testing, it was found that the two average similarity test was obtained and the two average difference test was obtained. The similarity test results of two averages prove that there are differences in the average learning outcomes in the experimental class and the control class. Test results of the difference between the two averages prove that the average learning outcomes in the experimental class are higher than in the control class. The application of the TGT (Teams Games Tournament) model accompanied by modification dominoes has an effect on learning outcomes in the scope of biology material for grade X students of SMA Negeri 1 Kibang.